Concept Kharkiv Smart City - Strizhkova, A.; Karbovska, K. (Baltic International Academy, 2018)
Робота присвячена критичному аналізу різних підходів до визначення концепції «Розумного міста», формулюванню дефініції «Kharkiv Smart City» та пропозиції її використання при розробці стратегій Smart City та планів або дорожніх карт з реалізації стратегій Smart City. // The work is devoted to a critical analysis of different approaches to defining the concept of "Smart City", formulating the definition of "Kharkiv Smart City" and proposing its use in the development of Smart City strategies and plans or roadmaps for the implementation of Smart City strategies.
Keywords: Smart City; concept of Smart City; Kharkiv Smart City; концепція Smart City; Харків Smart City